Neuroprotection And Neurodegenerative Diseases – A Review Article - Dr. Praveen Kumar; Dr. Vishwadeepak kimothi; Miss Sushila rawat; Sneha kumari (Revista Electronica de Veterinaria, 2024)
This paper will focus on neuroprotective effects of various drugs such as beta blockers and various natural products in the treatment of neurodegenerative disorder. We can define neuroprotection refers to recovery or regeneration of the nervous system, its cell, structure and function. Various neurodegenerative disorder such as Alzheimers disease which is characterized by progressive neuronal loss which can be treated with neuroprotective effects of beta blockers in a preclinical model of neurodegenerative disorder. Neuroprotective effects of various drugs are available only for limited indications. Development of new drugs require evaluation in animal studies, and human clinical trials. By the help of various natural products and suitable drug dosage neurodegenerative disorder can be improved. With few available treatments, Neurodegenerative illnesses are distinguished by a steady loss of neurons, as well as mental decline- present a serious threat to public health. Beta- blockers, commonly used to manage cardiovascular conditions, have been suggested to possess neuroprotective properties through their modulation of various cellular pathways implicated in neurodegeneration .While current treatment options primarily manage symptoms, the search for therapies that can slow or prevent disease progression remains a critical area of research. High blood pressure is treated with a class of medications known as beta blockers commonly administered, have emerged as potential candidates with neuroprotective properties.